Collected novels : the New York trilogy, in the country of last things, moon palace - Auster, Paul, 1947- (Faber and Faber, 2004)
The New York Trilogy is three variations on the classic detective story, that become an investigation into the art of storytelling and notions of identity.Moon Palace moves from Manhattan to the cruelly beautiful landscape of the American West to tell the story of three generations and examine America, art and the self.In the Country of Last Things offers a hunting picture of a devastated futuristic world-but one which may be seen to shadow our own.